2016
DOI: 10.3324/haematol.2015.137083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of renal impairment in MM-003, a phase III study of pomalidomide + low - dose dexamethasone versus high - dose dexamethasone in refractory or relapsed and refractory multiple myeloma

Abstract: Pomalidomide + low-dose dexamethasone is effective and well tolerated for refractory or relapsed and refractory multiple myeloma after bortezomib and lenalidomide failure. The phase III trial MM-003 compared pomalidomide + low-dose dexamethasone with high-dose dexamethasone. This subanalysis grouped patients by baseline creatinine clearance ≥ 30 -< 60 mL/min (n=93, pomalidomide + low-dose dexamethasone; n=56, high-dose dexamethasone) or ≥ 60 mL/min (n=205, pomalidomide + low-dose dexamethasone; n=93, high-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“… 11 , 12 , 13 The efficacy and tolerability of pomalidomide were maintained in all subgroups, including the elderly, 14 patients with high-risk cytogenetics 15 , 16 and those with moderate renal impairment. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 13 The efficacy and tolerability of pomalidomide were maintained in all subgroups, including the elderly, 14 patients with high-risk cytogenetics 15 , 16 and those with moderate renal impairment. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Recently published analyzes of these trials demonstrated that pomalidomide plus low-dose dexamethasone is also safe and effective in patients with moderate renal impairment. 23,24 Here, we report a pooled analysis from these three clinical trials (MM-002, MM-003, and MM-010) that further examined the safety profile of pomalidomide plus low-dose dexamethasone-including the incidence and time to onset of the AEs of interest (hematologic AEs, infections, neuropathy, and thrombotic events)-in patients with RRMM and to assess AE management in this population.…”
Section: Hematologic Aes and Infections Were The Most Common Grade ≥mentioning
confidence: 99%
“…Hematologic AEs and infections were the most common grade ≥ 3 AEs reported in these trials. Recently published analyzes of these trials demonstrated that pomalidomide plus low‐dose dexamethasone is also safe and effective in patients with moderate renal impairment …”
Section: Introductionmentioning
confidence: 99%
“…There are few data on the reversal of renal impairment with these agents. However, a retrospective subgroup analysis of a phase 3 trial assessed renal recovery comparing pomalidomide with low-dose dexamethasone to high-dose dexamethasone in patients with MM refractory or relapsed after bortezomib and lenalidomide (36). Despite improved disease-free survival with the use of pomalidomide, in 149 patients with an eGFR of ,60 ml/min before treatment, there was no difference in the rate of renal recovery between the two groups (42% and 47%, respectively.…”
Section: Chemotherapy and Stem Cell Transplantationmentioning
confidence: 99%